Trend Analysis of the Indian Capital Market - Tulsian, R. P.; Shrivastav, Rohit Kumar (Indian Journal of Research in Capital Markets, 2020)
In the present world, not only trade barriers are being removed, but the reduction in capital control norms can also be experienced. Basically, the changed world economic outlook has totally transformed the perception of investors too in the light of these recent policies. It has been experienced in the past that investors did not only show cautious behaviour, but also tried to invest in other countries too apart from their own country. This has increased the scope of foreign capital inflow, which is much needed for the development of the capital market of countries like India. The present study conducted a trend analysis of the Indian capital market. For this purpose, based on the review of literature, six variables were identified namely, debt private placement offerings, rights issue offering, preferential equity, overseas capital market offering, buyback offering, and further public issue (FPO) and data were gathered for the period from January 2001 – December 2019. Further, growth rate analysis on the basis of cumulative annual growth rate (CAGR) and graphical analysis has been conducted. From the analysis and interpretation, it was observed that the market segments : debt private placement offerings, rights issue offering, preferential equity, overseas capital market offering, buyback offering, and further public issue (FPO) of the capital market drove the market, and as a result, the Indian capital market showed a positive growth rate during the period from 2001 – 2019. Further, these segments reported a growing trend in the market, which actually helped the capital market to grow over time.